1985
DOI: 10.1111/j.1348-0421.1985.tb00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Studies on the Mycobacterium tuberculosis Series

Abstract: Numerical classification of slowly growing mycobacteria, including 159 strains received as Mycobacterium tuberculosis, M. bovis, M. africanum, and M. microti, was carried out using 88 characters, and the following results were obtained. 1) All 159 strains received as M. tuberculosis, M. bovis, M. africanum, and M. microti formed one cluster, and no clear-cut differentiation among these four species was achieved. These four species should be reduced to one species, M. tuberculosis. 2) Within the cluster, two su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…A study looking for variation in the 16S-to-23S rDNA internal transcribed spacer demonstrated none between the species of the complex [43]. Isolates that showed phenotypic characteristics intermediate between M. tuberculosis and M. bovis have been described [5] and analysis of a large series of phenotypic characteristics showed 92 % similarity between M. tuberculosis, M. bovis, M. africanum and M. microti [44]. Under the taxonomic rules M. bovis should be reduced to a biovar of M. tuberculosis rather than be classified as a discrete species [3].…”
Section: Resultsmentioning
confidence: 99%
“…A study looking for variation in the 16S-to-23S rDNA internal transcribed spacer demonstrated none between the species of the complex [43]. Isolates that showed phenotypic characteristics intermediate between M. tuberculosis and M. bovis have been described [5] and analysis of a large series of phenotypic characteristics showed 92 % similarity between M. tuberculosis, M. bovis, M. africanum and M. microti [44]. Under the taxonomic rules M. bovis should be reduced to a biovar of M. tuberculosis rather than be classified as a discrete species [3].…”
Section: Resultsmentioning
confidence: 99%
“…pinnipedii, the dassie bacillus, and "M. canettii" (proposed name) (3,5,6,26). Although the members of the complex may differ in their epidemiologies, host spectra, geographic ranges, pathogenicities, and antituberculosis drug susceptibilities and although they display different phenotypic characteristics by conventional biochemical tests, they show high degrees of genetic homogeneity (10, 25).…”
Section: The Mycobacterium Tuberculosis Complex (Mtb Complex) Consistmentioning
confidence: 99%
“…Previous logical arguments have suggested that all members of the M. tuberculosis complex are sufficiently similar to belong to the species M. tuberculosis (Wayne, 1984;Tsukamura et al, 1985;van Soolingen et al, 1997). Acceptance of such an approach would cause currently accepted species (M. bovis, M. microti and M. africanum) to warrant classification at the subspecies level.…”
Section: Introductionmentioning
confidence: 99%